PERSEPSI PESERTA DIDIK TERHADAP 10 KETERAMPILAN MENGAJAR GURU BIOLOGI PRAKTEK LAPANGAN (PL) DI SMAN 1 BUKITTINGGI - Rahmi, Ennike Gusti (Perspektif Pendidikan dan Keguruan, 2021)
The purpose of this study was to find out students' perception of the teaching skills of field practice biology teachers (PL) at SMAN 1 Bukittinggi. This research is descriptive research. The sampling technique used is Random Sampling, where each class is sampled for 20% of the total number of students. Thus from the population of mipa students in grade X and XI SMAN 1 Bukittinggi in the 2018/2019 school year amounted to 273 students spread across 8 locally, sampled by 20% of 56 students. The data obtained is processed using percentage technique (%). Based on the analysis of data obtained from the results of the study, it is known that students' perception of the teaching skills of field practice biology teachers in SMAN 1 as a whole is good with a percentage of 82.25%. While reviewed from each sub-variable described as follows: 1) Skills of opening and closing learning with a percentage of 85.14%, good category; 2) Skills managing classes with a percentage of 77,68%, category is quite good; 3) Reinforcement skills with a percentage of 74,25%, the category is quite good; 4) Skills guiding small group discussions with a percentage of 79,51%, a pretty good category; 5) Questioning skills with a percentage of 82.71%, good category; 6) Skill explaining with percentage 81.28, good category; 7) Skills held variasai with a percentage of 79.21%, the category is quite good; 8) Teaching skills of small groups and individuals with a percentage of 78,20%, the category is quite good; 9) Skills to develop and use learning media with a percentage of 82.42%, good category; 10) Esq developing skills with a percentage of 78.42%, the category is quite good.